(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2026)
This paper explores the physiological and psychological impacts of nighttime physical exercise, defined as activity occurring between 9:00 PM and 6:00 AM. The study examines the complex relationship between exercise timing, circadian rhythms, and health outcomes, with a specific focus on neurological risks such as Parkinson’s disease. While traditional guidelines often warn against late-night activity, emerging evidence suggests that moderate nighttime exercise can improve sleep duration and regularity if timed appropriately. Furthermore, the paper discusses the influence of chronotypes on cognitive performance and academic achievement, along with critical safety considerations regarding visibility and environmental hazards during nocturnal activity. The findings emphasize the need for personalized exercise routines that integrate restorative practices and environmental adjustments to optimize overall well-being.